Discrimination experienced by Aboriginal and Torres Strait Islander males in Australia: Associations with suicidal thoughts and depressive symptoms. (June 2022) - Haregu, Tilahun; Jorm, Anthony F; Paradies, Yin; Leckning, Bernard; Young, Jesse T; Armstrong, Gregory
Introduction: Globally, Indigenous populations have higher rates of suicidal behavior and psychological distress compared to non-Indigenous populations. Indigenous populations also report high rates of exposure to discrimination, which could potentially contribute to poor mental health outcomes. The objectives of this paper were to estimate the prevalence of discrimination among Aboriginal and Torres Strait Islander males in Australia and to examine the role of discrimination in the association between Aboriginal and Torres Strait Islander status and suicidal thoughts and depressive symptoms. Methods: We used cross-sectional data on 13, 697 males aged 18–55 years from the Australian Longitudinal Study on Male Health. We undertook a Poisson regression with robust standard error analyses to examine Aboriginal and Torres Strait Islander status and self-perceived exposure to discrimination in the past 2 years as correlates of recent suicidal ideation. We used zero-inflated negative binomial regression to assess Aboriginal and Torres Strait Islander status and self-perceived exposure to discrimination as correlates of recent depressive symptoms. Results: Aboriginal and Torres Strait Islander males have a twofold higher prevalence of self-perceived discrimination (39.2% vs 19.3%, p  < 0.001), suicidal ideation (21.8% vs 9.4%, p  < 0.001) and moderate or worse depressive symptoms (24.0% vs 12.2%, p  < 0.001) as compared to their non-Indigenous counterparts. After adjusting for sociodemographics and substance use, Aboriginal and Torres Strait Islander status was significantly associated with suicidal thoughts (odds ratio = 1.49, p  = 0.019) and depressive symptoms (prevalence rate ratio = 1.19, p  = 0.018). About 15.3% and 28.7% of the association between Aboriginal and Torres Strait Islander status and suicidal thoughts and depressive symptoms, respectively, was explained by discrimination. Conclusion: Our analyses add to evidence that discrimination is a contributor to mental health disparities between Aboriginal and Torres Strait Islander and non-Indigenous populations in Australia. Reducing discrimination ought to be considered as part of strategies to improve the social and emotional well-being of Aboriginal and Torres Strait Islander people.